INTERNATIONAL EXPERIENCE OF HUMAN CAPITAL DEVELOPMENT AT THE LEVEL OF THE TERRITORIAL COMMUNITY - Rybka, Andriy (International Journal of Innovative Technologies in Social Science, 2021)
Today, domestic scientists are carefully studying the process of development of the newly created united territorial communities, analyzing their main problems and challenges. However, it would be appropriate to combine such analysis with best international practices, which should help to increase the efficiency of the decentralization process in Ukraine and increase its effectiveness by taking into account both the advantages and disadvantages of international experience of community development in the frameworks of decentralization. Thus, the main tasks of the article are: to study the process of development of territorial communities of the European Union, to identify long-term areas for implementing the best international practice in Ukraine and to develop recommendations for human capital development at the local community level in the frameworks of decentralization.Although the active process of decentralization began in Ukraine in 2014, our country is still in the process of reforming local self-government and decentralization of powers, which makes it especially important and relevant to study the experience of other countries. The issue of decentralization remains a key issue for the further formation of Ukraine's strategic development, however, the adoption of international models requires taking into account the specifics of the development of the state by itself. Since the current system of territorial community’s operation in Ukraine is not perfect and still at the initial stage of its development, studying the experience of foreign countries will allow us to draw some conclusions about the prospects for further local communities development in Ukraine and to identify key areas of effective operation of territorial communities in Ukraine.